DEVELOPING WORKSHEET BASED ON HOTS FOR SIXTH GRADE ELEMENTARY SCHOOL STUDENTS IN THE SECOND SEMESTER - Made Satya Raditya; Putu Kerti Nitiasih; Ni Komang Arie Suwastini; Rahayu Budiarta (LP3M Universitas PGRI Mahadewa Indonesia, 2021)
This study aims to develop a HOTS-based student worksheet for grade 6 elementary school students. This study uses Design and development (D&D). It applies the ADDE (Analysis, Design, Development, and Evaluation) model, which Rich and Klein found in 2007. To obtain data using the subject in grade 6 elementary school. The method used is quantitative and qualitative in finding data. The instruments used in this research are syllabus, observation sheet, interview guide, expert judgment rubric, and questionnaire. The subject of this research is a teacher and student. The product results, which is still a prototype, showed that it is very relevant from the expert jury. In looking for quality, six users were taken, including one teacher and five students who played a role in assessing the quality of the developed worksheet. The results given from the quality indicate that the student worksheets can be categorized as an “Good worksheet,” which means that the student worksheets can increase students' ability to think higher-order (HOTS).